All In: Teachers' and College Faculty's Roles in Recruiting Future Physical Educators. Issue 4 (3rd May 2016) - Woods, Amelia Mays; Richards, K. Andrew R.; Ayers, Suzan F.
Abstract : A 10-year trend of nationwide decreases in teacher preparation enrollments has been notable in physical education teacher education (PETE) programs. Many factors have been offered as an explanation for this drop, including the convenience of online options, a strained economy, political factors, and widespread "teacher bashing." This article uses the acculturation phase of occupational socialization theory to examine how the physical education profession can effectively recruit prospective teachers. Actions are suggested for K–12 physical educators and PETE professors, both independently and in collaboration, that could foster young people's interest in the profession. The strategies physical educators could implement include engaging potential recruits in conversations about the physical education profession, providing teaching assistant opportunities, and setting up campus visits for students expressing interest in the profession. College/university faculty can also recruit undeclared students, nurture current PETE candidates, collaborate with local junior-college faculty and advisors, and use inservice professional development opportunities to connect with potential recruits. While none of these is the "silver bullet" to retaining a profession, each provides a way current physical education professionals may contribute to the growth of our field.